Intelligent Real-Time Air Quality Monitoring with ESP Technology: A State-of-the-Art Approach for a Sustainable Future - Engr. Shazia Feroz; Basit Ahmad; Engr. Moeed Furrukh, (Dialogue Social Science Review (DSSR), 2025)
Pollution is the major issue worldwide in which Air pollution, considered the major concern which is the most dangerous and severe pollution among all the others i.e., water pollution, noise pollution, thermal pollution etc. Air pollutants are responsible for various health problems such as asthma, heart attacks, lung cancer etc. Monitoring these pollutants is very important because it then add to the air in the shape of air pollution which directly effects the human health. This will able the environmental planners to design and develop some new policies and develop public awareness. The project aims to deploy the efficient power usage, low cost, small size compact system, high accuracy. (RAQMS) Real-time Air Quality Monitoring System is a combination of hardware which includes Gas sensors (CO, NO2, SO2, Smoke) Temperature and Humidity sensors and a microcontroller ESP-32, Server, and android application. It is used for the interfacing with the equipment’s where Real-time Index (RQI) are measured and transferred it to the centralized system through IOT (Internet of Things) where it is monitored on Lab View (software) Real-time platform. The measured data will be in real time and according to the standard values, based upon the parameters considered as standard which will give the indication about the environment condition either polluted or safe. The goal is to make pollution level estimation, share data and interfaces to design the air quality models, support research and also make this project as less costly as we can so that the people belong to any background and society, can use it. If researchers want to improve its efficiency by investing some amount for the further research. It will turn out to be a less costly and most compact solution as a weather station for the air quality monitoring.